Space Vector Pulse Width Modulation for Three-level Indirect Matrix Converter to Eliminate Common Mode Voltage - Nguyen, Dinh Tuyen (Old Journal, 2019)
This paper presents the pulse width modulation for multilevel indirect matrix converter for elimination common-mode voltage. The presented multilevel indirect matrix converter is based on the combination of T-type multilevel inverter and two cascaded rectifiers. Beside possessing the advantages of conventional matrix converter such as: sinusoidal input/output currents, bidirectional power flow, the multilevel indirect matrix converter provides some advantages: high performance of output voltage due to it is three-level voltage. The common mode voltage is responsible for overvoltage stress to the winding insulation and bearing damage of ac motor and it raises leakage currents, which can cause electromagnetic noise to the equipments installed near the converter. Therefore, the space vector modulation method is proposed in this paper to eliminate the common-mode voltage. In order to verify the theory analysis, some simulation results with Psim software are provided. Furthermore, one laboratory prototype was built and experimental results are presented to validate the simulation results.